Redox modifications of cysteine residues regulate the cytokine activity of HMGB1 - Huan Yang; Peter Lundbäck; Lars Ottosson; Helena Erlandsson-Harris; Emilie Venereau; Marco E. Bianchi; Yousef Al-Abed; Ulf Andersson; Kevin J. Tracey (BMC, 2021)
Abstract Background High mobility group box 1 (HMGB1) is a nuclear protein with extracellular inflammatory cytokine activity. It is passively released during cell death and secreted by activated cells of many lineages. HMGB1 contains three conserved redox-sensitive cysteine residues: cysteines in position 23 and 45 (C23 and C45) can form an intramolecular disulfide bond, whereas C106 is unpaired and is essential for the interaction with Toll-Like Receptor (TLR) 4. However, a comprehensive characterization of the dynamic redox states of each cysteine residue and of their impacts on innate immune responses is lacking. Methods Primary human macrophages or murine macrophage-like RAW 264.7 cells were activated in cell cultures by redox-modified or point-mutated (C45A) recombinant HMGB1 preparations or by lipopolysaccharide (E. coli.0111: B4). Cellular phosphorylated NF-κB p65 subunit and subsequent TNF-α release were quantified by commercial enzyme-linked immunosorbent assays. Results Cell cultures with primary human macrophages and RAW 264.7 cells demonstrated that fully reduced HMGB1 with all three cysteines expressing thiol side chains failed to generate phosphorylated NF-КB p65 subunit or TNF-α. Mild oxidation forming a C23-C45 disulfide bond, while leaving C106 with a thiol group, was required for HMGB1 to induce phosphorylated NF-КB p65 subunit and TNF-α production. The importance of a C23-C45 disulfide bond was confirmed by mutation of C45 to C45A HMGB1, which abolished the ability for cytokine induction. Further oxidation of the disulfide isoform also inactivated HMGB1. Conclusions These results reveal critical post-translational redox mechanisms that control the proinflammatory activity of HMGB1 and its inactivation during inflammation.